Pleurostomophora richardsiae associated with trunk diseases of grapevines in southern Italy - CARLUCCI, Antonia; CIBELLI, Francesca; LOPS, Francesco; PHILLIPS, Alan; CICCARONE, Claudio; RAIMONDO, Maria (Phytopathologia Mediterranea, 2015)
Pleurostomophora richardsiae (Nannf. apud Melin & Nannf.) L. Mostert, W. Gams & Crous was previously known mainly as a human pathogen. However, more recently this fungus has been isolated from wood tissue of grapevines that show Petri and esca disease symptoms in California (USA) and South Africa. During an assessment carried out in southern Italy, the abundant presence of this fungus was demonstrated by morphological, cultural and molecular means. Pleurostomophora richardsiae was isolated from sub-cortical wood patches and streaking of trunks and cordons of grapevine cultivars that showed decline and dieback symptoms. To understand its putative pathogenic role, pathogenicity tests were conducted in greenhouse experiments, where young grapevine plants of two cultivars were artificially inoculated with two isolates each of Pl. richardsiae, Lasiodiplodia theobromae and Phaeoacremonium aleophilum. Within 130 d, all three fungi produced brown streaking in both grapevine cultivars. The L. theobromae and Pl. richardsiae isolates were the most aggressive. Although the Pm. aleophilum isolates were pathogenic, they induced less severe wood streaking than the other two fungi. Therefore, Pl. richardsiae is considered a fungal pathogen of grapevine. All three fungal species were re-isolated from discolored tissue of all inoculated shoots, thus fulfilling Koch’s postulates.